Uneven opening of China's society, economy, and politics: pro-growth authoritarian governance and protests in China - Lai, Hongyi (Taylor & Francis (Routledge), 2010)
This article evaluates China's model of development, especially its main component, i.e. its model of governance. It suggests that China's model of development is marked by an imbalance between fast opening of the economy and the society and sluggish opening of the political system. The Chinese society has become much more open, reflected in the Chinese growing awareness of their legal rights. The Chinese economy has become highly internationalized and open, but much of Chinese politics is closed. China's governance is marked by pro-growth authoritarianism. The Chinese state is effective in opening up the economy, promoting reform, and generating economic growth, but offers weak protection of people's rights and ineffectual mitigation of social grievances. These imbalances help produce social protests. Viable solutions are discussed.